Problematika Pendidikan Kesetaraan Pada Masyarakat Desa Singkuang, Kecamatan Muara Batang Gadis, Kab.Mandailing Natal, Sumatera Utara - Safitri, Adinda; Indria Nora Harahap, Friska; Maritan, Elisabet (Program Studi Pendidikan Luar Sekolah, 2022)
The lack of educational infrastructure and also low public awareness of education, due to economic factors, makes the dropout rate high. Due to the high dropout factor, the authors are interested in conducting research on equality education in Singkuang village, Mandailing Natal, North Sumatra. This study uses a descriptive qualitative approach. The data collection technique carried out in the village is by distributing online questionnaires to the people in Singkuang village. Based on research that has been carried out by observation and distributing google forms online, the authors found several factors causing equality education in Singkuang village, namely: The lack of educational facilities and infrastructure in Singkuang village and also the lack of knowledge and socialization about equality education to people who is in Singkuang village. Efforts made by the author to overcome the problem of equality education in Singkuang village are by conducting outreach to the Singkuang village community about the importance of equality education for those who drop out of school in order to get their education back and can help people find work in order to fulfill their life needs.